1997
DOI: 10.1021/jm9606610
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of Thyroid Hormones by Variable Temperature Nuclear Magnetic Resonance:  The Role of Side Chain Rotations and Cisoid/Transoid Interconversions

Abstract: 1H NMR spectra of the thyroid hormone thyroxine recorded at low temperature and high field show splitting into two peaks of the resonance due to the H2,6 protons of the inner (tyrosyl) ring. A single resonance is observed in 600 MHz spectra at temperatures above 185 K. An analysis of the line shape as a function of temperature shows that the coalescence phenomenon is due to an exchange process with a barrier of 37 kJ mol-1. This is identical to the barrier for coalescence of the H2',6' protons of the outer (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…For all of these compounds, diastereotopic or diastereoisomeric signals of groups carried by the unsymmetrical ring remained unresolved even at −90 °C in CD 3 OD, thus suggesting20 barriers to racemization or epimerization at least as low as 36–38 kJ mol −1 21. The corresponding half‐life for racemization or epimerization for these compounds is probably20 less than 10 −6 s, a factor of 100 000 shorter than for even the fastest racemization of the comparable ethers 7 bearing only one isopropyl group at R 1 and comparable with the rate of ArOAr rotation in thyroxine,7 a di‐ ortho ‐substituted diaryl ether.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…For all of these compounds, diastereotopic or diastereoisomeric signals of groups carried by the unsymmetrical ring remained unresolved even at −90 °C in CD 3 OD, thus suggesting20 barriers to racemization or epimerization at least as low as 36–38 kJ mol −1 21. The corresponding half‐life for racemization or epimerization for these compounds is probably20 less than 10 −6 s, a factor of 100 000 shorter than for even the fastest racemization of the comparable ethers 7 bearing only one isopropyl group at R 1 and comparable with the rate of ArOAr rotation in thyroxine,7 a di‐ ortho ‐substituted diaryl ether.…”
Section: Methodsmentioning
confidence: 96%
“…McRae et al in 19545a commented that compounds of type 1 “show, in wooden models, an unusually great degree of steric hindrance about the diphenyl ether linkage”. Dahlgard and Brewster5b proposed in 1958 that diaryl ethers might exist as separable atropisomers, and some sub‐atropisomeric barriers to bond rotations were measured in a small range of compounds 1 ,6, 7 but it was not until 1998 that Fuji and co‐workers8 resolved three examples of 2 , the only non‐macrocyclic diaryl ethers that have yet proved to be atropisomeric. Herein, we report the synthesis, stereochemistry, stereodynamics, and stereoisomeric separation of a set of simple diaryl ethers and deduce some empirical rules to describe the requirements for chirality in this class of molecule.…”
Section: Methodsmentioning
confidence: 99%
“…For these compounds the photoisomerization is driven possibly by an in-plane inversion process (pyramidal inversion process of a C=N or an N=N bond) centered at one nitrogen atom.The implication of one-photon two-bond isomerization in the above mechanisms, has led the community [3d, 5] to suggest that the key step of the photoisomerization reaction is a radiationless transition between the S 1 and S 0 states; that is, the initially formed Franck-Condon excited conformer lowers its energy across the S 1 potential surface through twisting one double bond until it reaches the perpendicular structure, which is subsequently funneled through the S 1 /S 0 conical intersection (CI) to the ground surface, at which the concerted motion is completed. Concerted rotation about two bonds in the ground state (thermally) has been commonly observed in condensed-phase media for a variety of compounds, including artificial molecular rotors in unhindered environments, [6] conformationally flexible polymers, [7] organic chromophors, [8] biomolecules, [9] and so forth.Nevertheless, to the best of our knowledge, there is no evidence on whether concerted rotation about two bonds could drive an isomerization on a purely adiabatic excited surface. It is generally believed that for adiabatic cis-trans photoisomerization reactions-in which the CI evidently is not present-the one-photon one-bond isomerization OBF mechanism is the dominant pathway regardless of the nature of the medium.Previously it has been shown that 2-methoxynaphthalene (1) can exist in the gas and liquid phase in two different spectrally distinct conformations cis (syn) and trans (anti), which may interconvert torsionally (around the C aryl PO "double" bond by 1808) both thermally [10] and photochemically [11] (Scheme 1).…”
mentioning
confidence: 99%
“…The conformational features of T 4 have been long discussed in the literature and are still considered the most important properties for understanding the mechanism of its biological activity 10,13,37–39. Our results have revealed two new conformations of T 4 .…”
Section: Discussionmentioning
confidence: 51%